Designing of a pick and place robot mechanism for industrial usage - Jayawardena, Kodikara Arachchige Malithi; Lin, Than; Bohez, Erik L.J. (Pathum Thani, Thailand : Asian Institute of Technology, 2014)
Robots are used for optimization of a certain task through advanced technology to gain better results than the manual performance of that certain task. Pick and place robots are used in industries for betterment of the industries by improving the quality of the work done. These robots provide the users with faster, accurate, precise, cost effective solutions. This project is a design and a simulation of a pick and place robotic mechanism concept for an industrial application solely using Mechatronics Concept Designer {u2013} NX 8.5 software. Mechatronics concept designer software supports modeling and simulation of Mechatronics designs with automation associated activities and multi-body physics. This software allows users to do all mechanical, electrical and software related designing, everything at one platform. The design and the mechanism are applied for a factory based situation and the problem approach is taken from a real industrial situation. The whole system and the robot arm design along with its performance is modeled and simulated using the Mechatronics Concept Designer {u2013} NX8.5 software. Additional details such as the electrical system designs, Arduino program codes were done using the relevant software and added to enhance the solution developed using the Mechatronics Concept Designer {u2013} NX8.5 software. This report explains about the mechanical designs, electrical designs, Arduino program, and simulations, etc. which were created to accomplish the project objectives.
A capstone project submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Engineering in Mechatronics Engineering, School of Engineering and Technology
Capstone Project (B. Sc.) - Asian Institute of Technology, 2014
Keywords: Robots, Industrial